Eﬀect of growth regulators on the growth and yield of ginger (Zingiber oﬃcinale Rosc.) under polyhouse condition - Saljuna, K. P.; Thankamani, C. K.; Krishnamurthy, K. S.; Pavithran, Gayathri; Alagupalamuthirsolai, M. (Journal of Plantation Crops, 2023)
The experiment has been conducted to resolve the poor partitioning of dry matter towards rhizome by using plant growth regulators (PGRs). Therefore, two pot culture experiments were conducted during 2020-22 using the variety IISR Varada to investigate the eﬀects of foliar application of PGRs (6-BAP, cycocel, GA3 and PBZ at five diﬀerent concentrations viz. control, 50ppm, 100ppm,150ppm and 200ppm in three replications) on growth and yield. The experiment was laid out in Factorial CRD design under polyhouse condition. The results revealed that 6-BAP at 100ppm significantly increased the number of tillers, secondary rhizomes, tertiary rhizomes, length, diameter of rhizomes, and rhizome yield (322.3g/ plant) which is 240% more than the control.